Proposal of a new Maximum Lifetime Communication Model of Wireless Sensor Network - Lei, Jinhui; Tian, Xiyan (International Journal of Online and Biomedical Engineering (iJOE), 2016)
One new maximum lifetime communication model of wireless sensor network is proposed in this thesis and the model is based on conditions of base station with multiple sources and multiple links and the data generated from the source node can be transmitted to several base stations through multiple links. In this chapter, energy limitation and data stream conservation principles of a wireless sensor network are used to establish a linear planning model, and attaining the maximum lifetime of the network is the optimal objective to establish a model with multiple restrictions restricted by energy and bandwidth. The basic element influencing the lifetime of a wireless sensor network is the data forwarding rate. The lifetime of nodes will become longer with the decrease of node data. In this thesis, the data size of network nodes is taken as sub-optimization objective and the distributed heuristic algorithm will be used to solve the linear planning model. In the end, a simulation experiment is conducted to verify yhe performance of the communication model and indicate that the proposed model can effectively increase network lifetime.